g(c(

f(c(s(

f(f(

f(

R

↳Dependency Pair Analysis

G(c(x, s(y))) -> G(c(s(x),y))

F(c(s(x),y)) -> F(c(x, s(y)))

F(f(x)) -> F(d(f(x)))

Furthermore,

R

↳DPs

→DP Problem 1

↳Polynomial Ordering

→DP Problem 2

↳Polo

**G(c( x, s(y))) -> G(c(s(x), y))**

g(c(x, s(y))) -> g(c(s(x),y))

f(c(s(x),y)) -> f(c(x, s(y)))

f(f(x)) -> f(d(f(x)))

f(x) ->x

The following dependency pair can be strictly oriented:

G(c(x, s(y))) -> G(c(s(x),y))

There are no usable rules w.r.t. to the implicit AFS that need to be oriented.

Used ordering: Polynomial ordering with Polynomial interpretation:

_{ }^{ }POL(c(x)_{1}, x_{2})= 1 + x _{2}_{ }^{ }_{ }^{ }POL(G(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }

resulting in one new DP problem.

R

↳DPs

→DP Problem 1

↳Polo

→DP Problem 3

↳Dependency Graph

→DP Problem 2

↳Polo

g(c(x, s(y))) -> g(c(s(x),y))

f(c(s(x),y)) -> f(c(x, s(y)))

f(f(x)) -> f(d(f(x)))

f(x) ->x

Using the Dependency Graph resulted in no new DP problems.

R

↳DPs

→DP Problem 1

↳Polo

→DP Problem 2

↳Polynomial Ordering

**F(c(s( x), y)) -> F(c(x, s(y)))**

g(c(x, s(y))) -> g(c(s(x),y))

f(c(s(x),y)) -> f(c(x, s(y)))

f(f(x)) -> f(d(f(x)))

f(x) ->x

The following dependency pair can be strictly oriented:

F(c(s(x),y)) -> F(c(x, s(y)))

There are no usable rules w.r.t. to the implicit AFS that need to be oriented.

Used ordering: Polynomial ordering with Polynomial interpretation:

_{ }^{ }POL(c(x)_{1}, x_{2})= x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(F(x)_{1})= 1 + x _{1}_{ }^{ }

resulting in one new DP problem.

R

↳DPs

→DP Problem 1

↳Polo

→DP Problem 2

↳Polo

→DP Problem 4

↳Dependency Graph

g(c(x, s(y))) -> g(c(s(x),y))

f(c(s(x),y)) -> f(c(x, s(y)))

f(f(x)) -> f(d(f(x)))

f(x) ->x

Using the Dependency Graph resulted in no new DP problems.

Duration:

0:00 minutes